Role overload, knowledge acquisition and job satisfaction: An ambidexterity perspective on boundary-spanning activities of IT employees - Wang, Guofeng; Liu, Xiaojuan; Liu, Yipeng (International journal of human resource management, 2019)
Building upon the ambidexterity perspective, this study conceptualizes boundary-spanning activities as both transactional and learning to illuminate their different effects on IT employees' job satisfaction. Specifically, we offer an overarching theoretical framework rooted in ambidexterity by connecting the role theory and knowledge acquisition perspective to reconcile the inconsistency of extant findings. Role overload has a mediating effect on the relationship between boundary-spanning activities (both transactional and learning) and job satisfaction, whereas knowledge acquisition mediates the relationship between learning boundary-spanning activities and job satisfaction. Furthermore, high achievement motivation and learning goal orientation moderate the positive effect of learning boundary-spanning activities on job satisfaction. The quantitative analysis of IT employees in Chinese state-owned enterprises largely supports our hypotheses. We conclude this paper by discussing theoretical and managerial implications for ambidexterity, boundary spanning, and job satisfaction.